The status of Clinocera rufipes Bezzi, a new junior synonym of Clinocera nigra Meigen (Diptera: Empididae: Clinocerinae) - Sinclair, Bradley J. (Zootaxa, 2007)
During the latter stages of revisionary work on the genus Clinocera Meigen (Sinclair in prep.), the type series of most species were examined. In an earlier paper Sinclair (1999) compared European and North American types of the C. appendiculata group, which resulted in several redefinitions and synonyms. In this short correspondence, the results of an examination of a series of specimens from the original type series of C. rufipes Bezzi and the remaining syntype of C. nigra Meigen are also reported